A Novel Prognostic Stratified System Based on Tumor Budding and the Cell Nest Size in Ureter Urothelial Carcinoma - Jialin Li; Xinyue Li; Jing Yang (Applied Bionics and Biomechanics)
At present, malignant tumor stratification based on the TNM stage is very important for predicting patient prognosis and selecting appropriate treatment. The prognostic factor of ureter urothelial carcinoma is mainly based on the stage according to AJCC (8th) TNM classification. None of the histomorphologic features is recommended to assess patient’s prognosis. Recently, a novel three-tiered grading system based on tumor budding and the cell nest size (referred as TBNS system) has been applied to be highly prognostic for some squamous cell carcinomas, including esophageal, pulmonary, uterine cervix cancer, and endocervical endocarcinoma. In this study, we explored the application of this TBNS grading system in ureter urothelial carcinoma consisting 87 surgically resected cases and no neoadjuvant therapy. Tumor budding and the cell nest size were assessed and correlated with clinicopathological data and survival. The results showed that higher tumor budding, cell nest size, and TBNS grading system were strongly related to shorter overall survival (OS), disease-specific survival (DSS), and disease-free survival (DFS). Multivariate survival analysis showed the TBNS grading system to be closely related to the independent prognosis of DFS and DSS. In conclusion, the TBNS grading system based on tumor budding and cell nest size, if further validated, could satisfactorily predict the prognosis of uterine urothelial carcinoma and be applicable in routine pathologic description of this cancer type.